2019
DOI: 10.1016/j.yclnex.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive non-surgical locally injected vitamin C versus the conventional surgical depigmentation in treatment of gingival hyperpigmentation of the anterior esthetic zone: A prospective comparative study

Abstract: homogenous gingival color and needs tactile sensation. In addition, critical zones for injection have to be avoided. Conclusions: The current study examines the points of strength and weakness of both techniques in depth. The surgical technique is considered as the gold standard for management of gingival hyperpigmentation. The usage of vitamin C injection for depigmentation showed comparative results in comparison to the conventional technique. Furthermore, the usage of vitamin C could provide a long term sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
(43 reference statements)
1
10
0
2
Order By: Relevance
“…Our outcomes revealed excellent aesthetic results, and these were in agreement with Yussif et al [ 18 ] who used intraepithelial injections of 1-1.5 ml AA (200-300 mg) in the gingival mucosa and reported that its direct delivery reduced pigmentation incidence scores and area of pigmentation. As well as comparing injectable AA to conventional scalpel depigmentation by Yussif et al [ 19 ] in 2019 who concluded that injecting AA into pigmented cells presented comparable results to conventional surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Our outcomes revealed excellent aesthetic results, and these were in agreement with Yussif et al [ 18 ] who used intraepithelial injections of 1-1.5 ml AA (200-300 mg) in the gingival mucosa and reported that its direct delivery reduced pigmentation incidence scores and area of pigmentation. As well as comparing injectable AA to conventional scalpel depigmentation by Yussif et al [ 19 ] in 2019 who concluded that injecting AA into pigmented cells presented comparable results to conventional surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, gingival recession depth reduction and radiographic intra-osseous depth fill were significantly superior in the OFD+AA/PRF group. These findings could be explained by the additive role of AA to the PRF, boosting cellular pluripotency, proliferative and regenerative attributes of stem/progenitor cells, osteoblasts, fibroblasts [69,70] and G-MSCs [16,17]; its ability to increase extracellular matrix production [71]; the collagen biosynthesis of the periodontal ligament, gingiva, cement and alveolar bone [72,73]; and the expression of alkaline phosphatase and osteocalcin [74,75] as well as its potential to increase the proliferation of keratinocytes and fibroblasts, improving thereby the gingival phenotype [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…Este procedimiento se lo realiza bajo anestesia local y eliminando secciones delgadas, para evitar exponer el hueso subyacente; está contraindicado en áreas gingivales finas, donde se puede originar recesión gingival (5,36,37). Es considerada como el gold estándar (38,39), ofrece ventajas como la facilidad de aplicación, es económica, no requiere instrumental especial, tiempo quirúrgico reducido y el período de cicatrización es más rápido en comparación con otras técnicas. Tiene como desventaja la hemorragia durante y después de la cirugía, además el riesgo de infección (5,38,40).…”
Section: Cirugía Con Bisturíunclassified
“…El ácido ascórbico o Vitamina C, es eficaz en la despigmentación de los tejidos gingivales por vía tópica (gel) o transmucosa (infiltración); inhibe la síntesis de melanina al reducir la formación de dopaquinona (25,39,55). Es administrada hasta que los tejidos se tornen pálidos, se recomienda un máximo de 0,1 ml de ácido ascórbico por cada punción con 2-3 mm de separación (39). Para evitar la recidiva se realizan aplicaciones locales a intervalos semanales y luego mensuales (25).…”
Section: Métodos Químicosunclassified